2009
DOI: 10.1016/j.ejcts.2008.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve surgery plus concomitant atrial fibrillation ablation is superior to mitral valve surgery alone with an intensive rhythm control strategy☆☆☆

Abstract: Radiofrequency Maze ablation additional to mitral valve surgery resulted in a higher SR conversion rate (75%), despite control group treatment with intensive rhythm control strategy having a higher SR conversion rate (39%) compared to literature (approximately 25%). Maze ablation resulted in normalisation of atrial function in 63% of patients converted to SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 23 publications
1
79
0
1
Order By: Relevance
“…von Oppell et al [17] randomized 50 patients for mitral valve surgery with or without concomitant AF ablation. Those who remained in sinus rhythm had better scores on quality of life questionnaires and were more in free use of anticoagulants and antiarrhythmics.…”
Section: Discussionmentioning
confidence: 99%
“…von Oppell et al [17] randomized 50 patients for mitral valve surgery with or without concomitant AF ablation. Those who remained in sinus rhythm had better scores on quality of life questionnaires and were more in free use of anticoagulants and antiarrhythmics.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were assessed at 6 months after their surgeries for a number of clinical parameters in addition to physical functioning, general health, vitality, and social functioning. 23 Scores on all these domains increased significantly after surgery for all patients and did not differ between treatment groups. 23 In contrast to most of these studies, in the present study, we specifically assessed HRQL in a larger sample size at 6 months and 1 year after surgery.…”
Section: Advantages Of Minimally Invasive Cardiac Proceduresmentioning
confidence: 89%
“…23 Scores on all these domains increased significantly after surgery for all patients and did not differ between treatment groups. 23 In contrast to most of these studies, in the present study, we specifically assessed HRQL in a larger sample size at 6 months and 1 year after surgery. Our results make a unique contribution to this area of research by directly measuring patient-reported HRQL after minimally invasive surgery with a validated and widely used psychometric instrument and identifying some of the factors that influence its improvement in relation to baseline values.…”
Section: Advantages Of Minimally Invasive Cardiac Proceduresmentioning
confidence: 89%
“…Several observational studies strongly suggests that surgical intervention is beneficial for return to sinus rhythm (54,56,57). The original Maze III cohort reported by Dr. Cox's group showed 95.9% and 97.5% freedom from AF at 5.4 years performed in lone and concomitant AF, respectfully (54).…”
Section: Sinus Restorationmentioning
confidence: 99%